2008
DOI: 10.1002/cne.21607
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin receptor‐like receptor (CLR), receptor activity‐modifying protein 1 (RAMP1), and calcitonin gene‐related peptide (CGRP) immunoreactivity in the rat trigeminovascular system: Differences between peripheral and central CGRP receptor distribution

Abstract: Calcitonin gene-related peptide (CGRP) is a key mediator in primary headaches including migraine. Animal models of meningeal nociception demonstrate both peripheral and central CGRP effects; however, the target structures remain unclear. To study the distribution of CGRP receptors in the rat trigeminovascular system we used antibodies recognizing two components of the CGRP receptor, the calcitonin receptor-like receptor (CLR) and the receptor activity-modifying protein 1 (RAMP1). In the cranial dura mater, CLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
221
5
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 291 publications
(264 citation statements)
references
References 158 publications
19
221
5
9
Order By: Relevance
“…30 Thus, localization of CGRP receptor components on mast cells may indicate that CGRP can act as a mild mast cell degranulator. 27 Together, the dural CGRP receptor distribution is in line with existing functional data and suggests targets important in our understanding of the pharmacologic effector sites of CGRP inhibitors. This forms the starting point in our understanding of the exact interplay of substructures in meningeal nociception and the relation to CGRP signaling and headache generation.…”
Section: Role For Cgrp Receptors In the Cranial Meningessupporting
confidence: 51%
See 3 more Smart Citations
“…30 Thus, localization of CGRP receptor components on mast cells may indicate that CGRP can act as a mild mast cell degranulator. 27 Together, the dural CGRP receptor distribution is in line with existing functional data and suggests targets important in our understanding of the pharmacologic effector sites of CGRP inhibitors. This forms the starting point in our understanding of the exact interplay of substructures in meningeal nociception and the relation to CGRP signaling and headache generation.…”
Section: Role For Cgrp Receptors In the Cranial Meningessupporting
confidence: 51%
“…Instead, CLR was co-localized with glial fibrillary acidic protein (GFAP) as a marker for glia, indicating that CGRP receptor components may be expressed by Schwann cells. 27 While the functional significance of CGRP receptors on Schwann cells is currently unexplored, findings of CGRP receptors on arterial blood vessels are in line with CGRP functions (Fig. 1A).…”
Section: Role For Cgrp Receptors In the Cranial Meningesmentioning
confidence: 48%
See 2 more Smart Citations
“…In rat STN, it was suggested that CGRP and its receptor components are localized in terminals from primary afferents [29]. In contrast, CLR did not co-localize with neuropeptides of primary spinal afferents in the dorsal horn of rat [30].…”
Section: Discussionmentioning
confidence: 99%